Design and Developmet of Remotely Operated a Small-Scale Waterways Cleaning Robot - Sazali, Nur Irdina; Shaari, Muhammad Farid (Progress in Engineering Application and Technology, 2024)
Water pollution has become a pressing global concern, as water bodies continue to be contaminated with various forms of debris such as plastics, trash, and other solid waste. This project aimed to design and development a small-scale waterways cleaning robots that could collect floating debris on the waterways. The design works including proposing suitable structure,navigation, garbage collecting mechanism, and locomotion of the robot. This project utilized PS2 wireless controller, to control the robot’s movements.Conduct a test to evaluate the buoyancy and debris collection performance of the waterways cleaning robot, ensuring it can effectively navigate and remove floating debris from the water’s surface. The results show that the robot can float and move with stable. Analysis on debris collection shows that plastic, bottle cap and dry leaves can be collected. In conclusion, the design and development of this remotely operated waterways cleaning robot have successfully achieved its objectives, providing a promising solution for maintaining clean waterways.